Malaysian property and construction companies: diversification potential, stock price behaviour and its response towards macroeconomic shocks - Nur Atiqah, Abdullah (2016)
This thesis investigates diversification benefits of investing in the property and construction stocks in Malaysia from 1995 to 2013 by using correlation analysis. Panel ARDL (autoregressive distributed lag) is used to examine the relationship between both sectors’ stock prices and their fundamental variables (NAV (net asset value), EPS (earnings per share) and DPS (dividend per share)), where it involves panel cointegration and error correction mechanism (ECM). Another objective of this thesis is to discover the impact of macroeconomic shocks on both sectors’ stock prices, which is investigated through the impulse response analysis and variance decomposition analysis. Annual data from twenty-eight listed property companies and sixteen listed construction companies are evaluated. Diversification benefits do exist between both sectors’ stocks. EPS is a significant fundamental variable for explaining both sectors’ stock price change while NAV is only significant in influencing property stock price changes. DPS is not relevant for both sectors. The ECM shows that both sectors’ stock prices move back to equilibrium at a fairly similar speed. The impulse response functions results indicate that interest rate changes influence stock prices the most while trade openness shocks have slight effects on the stock prices. Variance decomposition analysis found that the percentage movement in the stock prices is highest when shocked by interest rate changes while trade openness changes do not influence the stock prices significantly. The impact on property stock prices is higher to economic shocks compared to the construction sector. The findings could aid investors in making sound decisions about their investment as it is proven that they could benefit from investing in both sectors. Investors could look into the fundamental variables which are useful in determining the stock prices movements. Policy makers should control the interest rate adjustments, determine the GDP growth rate, monitor the inflation rate and trade openness policies as shocks to these variables are proven to affect stock prices significantly.